Assessing the Feasibility of 3D-Printed Moulds in Sustainable Plastic Brick Fabrication - Lim, Hooi Peng; bin Mohd Shah, Mohd Hamdan; bin Masnan, Mohd. Bakhrin (Universitas Negeri Padang, 2025)
Sustainable water-based food production systems are essential to meet the growing demand for food while preserving water resources and ecosystems. These systems should integrate practices that manage water efficiently, such as green water management. Such practices conserve water and ensure the production of nutritious food, contributing to food and water security. The correlation between these systems and the production of wave breakers moulds to produce plastic waste bricks lies in the shared goal of environmental sustainability. Plastic waste bricks, created by repurposing plastic waste into durable building materials, offer a solution to plastic pollution. These bricks can be used to construct wave breakers, which protect shorelines and prevent erosion. This project aimed to fabricate a 3D-printed wave breaker mould for sustainable plastic bricks. Experimental testing was carried out to investigate this mould’s feasibility. It has been deduced that using 3D-printed moulds for wave breakers can lead to innovations in coastal engineering, potentially improving the efficiency and effectiveness of wave energy dissipation and offering economic and environmental benefits. It is recommended that surface modification could be an alternative to improve the mould’s wear and friction impact.